Designing Integrated Program for Teaching Language, Literature, and Arts for Young Learners - Febrianti, Yusnita; Wulyani, Anik Nunuk; Kusumaningrum, Shirly Rizky; Sudarmanto, Joni Agung (Jurnal Pendidikan Humaniora, 2024)
Much research discussed the value of teaching additional language, literature, and the arts for young learners. Among the many benefits, some research mentioned the development of children’s knowledge, emotion, intellect, imagination, as well as reading habits. Collectively, most studies in this area suggested facilitating the teaching of language, literature, and the arts as a part of lesson planning in the classroom. However, in an ESL context such as Indonesia, the ideal situation for the incorporation of language, literature, and the arts is not easy to accomplish. Therefore, the study outlines a design of a program that integrates the teaching of language, literature, and the arts to young learners. In the process, an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model is employed. The study anchored the development of the program design based upon two important elements. First, the consideration of factors necessary as the value of the foundation of the program, such as age group, benefits, and the types of activities. Second, the categorization of the types of activities is divided into two divisions, namely the individual program and the combined program. The result of the study shows that while the value of the teachings of language, literature, and the arts has been acknowledged, we need to facilitate the learning into a well-structured program for a more optimum result.